2013
DOI: 10.1021/om4000133
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) and Palladium(II) Complexes with Chelating N-Heterocyclic Carbene Amidate Ligands: Interplay between Normal and Abnormal Coordination Modes

Abstract: A series of six Ni(II) and Pd(II) complexes of two bidentate and two tetradentate N-heterocyclic carbene (NHC)/amidate ligands have been prepared. The complexes are uncharged, with square-planar coordination geometries, and the ligands are bound via the NHC groups and the deprotonated amide nitrogen atoms. Pd(II) complexes were prepared for the bidentate ligands, and in each case, two chelating bidentate ligands were bound to the metal center, yielding cis/trans geometric isomeric forms. The Pd(II) complexes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 77 publications
1
23
1
Order By: Relevance
“…In the case of pro‐ligand 7 the imidazolium groups were substituted with sterically demanding tert ‐butyl wingtip groups, while for 8 both imidazolium units were linked via o ‐xylene units to form a macrocyclic molecule. Pro‐ligand 5 was prepared by the reaction of 2‐chloroacetyl‐aniline with 1,2‐dimethylimidazole, while pro‐ligands 6 and 7 were prepared in a similar manner from N,N ′‐ bis (2‐chloroacetyl)‐1,2‐phenylenediamine and the appropriate substituted imidazole, 1,2‐dimethylimidazole or 1‐ t ‐butylimidazole (Scheme ) …”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…In the case of pro‐ligand 7 the imidazolium groups were substituted with sterically demanding tert ‐butyl wingtip groups, while for 8 both imidazolium units were linked via o ‐xylene units to form a macrocyclic molecule. Pro‐ligand 5 was prepared by the reaction of 2‐chloroacetyl‐aniline with 1,2‐dimethylimidazole, while pro‐ligands 6 and 7 were prepared in a similar manner from N,N ′‐ bis (2‐chloroacetyl)‐1,2‐phenylenediamine and the appropriate substituted imidazole, 1,2‐dimethylimidazole or 1‐ t ‐butylimidazole (Scheme ) …”
Section: Resultscontrasting
confidence: 99%
“…1 H NMR analysis of 10 showed that both the imidazolium C4‐H and amide N–H proton signals of the pro‐ligand were absent, indicating deprotonation and coordination of these groups to the metal centre. These results are consistent with the complex being uncharged with two chelating ligands coordinated to the Pd(II) centre via the NHC groups and the deprotonated amide nitrogen atoms (amidate), as has been found previously for similar systems . The X‐ray crystal structure of 10 was obtained (Figure ) and this confirmed that the NHC groups were coordinated via the abnormal coordination mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the (533−534), [163] (535), [164] (536), [165] (543−544), [166] (545−546), [167] (548 [168]−557), [169] (558), [51] (559), [71] (560), [161] (561), [170] (562−563), [141] (565), [171] (566−567), [172] (568), [173] (569), [126d] (570−573), [174] (574), [175] (575−576), [176] (577), [177] (578), [178] (579), [106] (580−581), [179] (582−583), [151] (584−585), [180] (586−588), [181] (595−596), [182] (597−599), [183] (600−603), [184] (604), [185] (605−608), [186] (609), [185] (610−613), [187] (614−618), [188] (619−621), [189] (622−623), [185] (624−630), [190] (631), [191] (633−635), [192] (636), [193] (637), [194] (647) [195] and (648) [196] complexes were obtained by this pathway from the treatment of the free or the in situ generated NHC The third route is the oxidation method (Scheme 15) using which the (589−590), [197] (638) …”
Section: Neutral Chelated Ni(ii)−nhc Complexesmentioning
confidence: 99%
“…In the 1 H NMR spectrum, the signal of the NCHN proton of the abnormal carbene is exceptionally downfield shifted at δ = 9.75 ppm, close to that of the ligand precursor P-NHC × HBr (10.33 ppm), suggesting a relatively acidic proton. [42][43][44] Complex 2 can also be prepared directly from [Ru(OAc) 2 (PPh 3 ) 2 ] and 2 equiv. of P-NHC × HBr in THF in the presence of NaOAc (88% yield).…”
Section: Scheme 1: Syntheses Of Nhc and Anhc Ru Complexesmentioning
confidence: 99%